Employer Screening Costs, Recruiting Strategies, and Labor Market Outcomes: An Equilibrium Analysis of On-Campus Recruiting - Russell Weinstein (Institute of Labor Economics (IZA), 2017)
This paper analyzes labor market matching in the presence of search and informational frictions, by studying employer recruiting on college campuses. Based on employer and university interviews, I develop a model describing how firms choose target campuses given relevant frictions. The model predicts that with screening costs, the decision to recruit and the wage are driven by the selectivity of surrounding universities, in addition to the university's selectivity. The prediction has strong support using data from 39 finance and consulting firms and the Baccalaureate and Beyond. Structural estimation of an equilibrium model directly quantifies the impact of reducing screening costs.
Keywords: J23; J31; D83; I26; M51; 330; labor market search; employer recruiting; return to university education; screening costs